AN INSIGHT INTO CHANGE MANAGEMENT IN A GLOBAL TRAVEL INDUSTRY - Wulida Afrianty, Tri (FIA UB, 2020)
This study aims to give an insight into how a global travel agent company, Flight Centre, manages change. Specifically, to gain an understanding as to how and why they make decisions around change, how they gain commitment to change from employees, how they use culture and communication in the change process. The primary data for this research was collected from face-to-face interview and telephone conversations. A total of 4 Flight Centre leaders (1 area leader from Victoria and 3 team leaders from Port Melbourne, Chadstone and Elsternwick stores) were interviewed. A total of 10 Flight Centre employees from Port Melbourne, Chadstone, Elsternwick and Brighton were interviewed informally in stores and on the phone.Â The result shows that Flight Centre is an example of a company that has made change a part of their day-to-day operations and have been very successful in changing and adapting in an industry that has seen a lot of organisations demise.